2019
DOI: 10.4018/978-1-5225-8535-0.ch017
|View full text |Cite
|
Sign up to set email alerts
|

The Pragmatics of Political Deception on Facebook

Abstract: Facebook, an intrinsic part of 21st century social realities where cognitive-participatory activities are largely captured, is consistently explored for political deception. This chapter investigates how participants utilize language to deceive politically the Nigerian electorate on Facebook. For data, 250 Facebook posts on Nigerian politics were sampled, out of which 50 were purposefully selected for being highly rich in deceptive content in order to unpack online deception through multimodal critical discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Studies in fake news in Nigeria cut across examining challenges in curtailing the spread of misinformation and disinformation in social media during elections (Assay, 2019) and pragmatic use of Facebook as a propaganda to deceive electorates (Olajimbiti, 2019). While Olajimbiti (2019) identifies four political deceptive forms on Facebook to include equivocation of identity, exaggeration of performance, falsification of corruption cases, and concealment of offences, Assay (2019) advocates strengthening national campaign against fake news to checkmate falsehood and half-truth. This study aims at examining discursive strategies used to justify falsehood in selected fake news items sampled from WhatsApp, Facebook and Twitter during the 2019 Nigerian general elections.…”
Section: Fake News Social Media and Politicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in fake news in Nigeria cut across examining challenges in curtailing the spread of misinformation and disinformation in social media during elections (Assay, 2019) and pragmatic use of Facebook as a propaganda to deceive electorates (Olajimbiti, 2019). While Olajimbiti (2019) identifies four political deceptive forms on Facebook to include equivocation of identity, exaggeration of performance, falsification of corruption cases, and concealment of offences, Assay (2019) advocates strengthening national campaign against fake news to checkmate falsehood and half-truth. This study aims at examining discursive strategies used to justify falsehood in selected fake news items sampled from WhatsApp, Facebook and Twitter during the 2019 Nigerian general elections.…”
Section: Fake News Social Media and Politicsmentioning
confidence: 99%
“…Fake news comprises fabricated information geared towards legitimating falsehood to achieve political gains. Studies in fake news in Nigeria cut across examining challenges in curtailing the spread of misinformation and disinformation in social media during elections (Assay, 2019) and pragmatic use of Facebook as a propaganda to deceive electorates (Olajimbiti, 2019). While Olajimbiti (2019) identifies four political deceptive forms on Facebook to include equivocation of identity, exaggeration of performance, falsification of corruption cases, and concealment of offences, Assay (2019) advocates strengthening national campaign against fake news to checkmate falsehood and halftruth.…”
Section: Fake News Social Media and Politicsmentioning
confidence: 99%
“…Al-Zawawy concluded that such models lack contextsensitivity and are therefore limited in determining whether a discourse is deceptive or nondeceptive. Olajimbiti (2019) surveyed the political deception in 250 sampled political posts on Facebook out of which 50 posts are selected as the most politically deceptive at the time of the Nigerian 2019 general elections. The posts were found to achieve other-criticism, positive selfpresentation, and mobilized the public, yet they fell short of addressing the ideology-laden motivations according to which politicians (re)act.…”
Section: Previous Studiesmentioning
confidence: 99%